EMOTIONAL BURNOUT AS A MODERATOR OF TV NEWS IMPACT ON YOUNG ADULT AUDIENCE: EEG STUDY - Volodymyr Rizun; Yurii Havrylets; Sergii Tukaiev; Maksym Khylko; Anatolii Vasilchenko (World Science, 2018)
The paper considers changes of the EEG parameters while viewing the emotionally accented TV messages depending the emotional burnout formation. We found that the character and degree of EEG changes during the perception of emotional stimuli significantly depend on the characteristics of a particular stimulus and the current level of emotional state of the viewers (emotional burnout, fatigue). The subjects with the phase of resistance of the emotional burnout syndrome at the stage of formation (“Burnout RP under development”) differ significantly from the groups with the unformed and formed Burnout Resistance Phase (“Burnout RP unformed”, “Burnout RP formed”) in the dynamics of changes of spectral power of the EEG subbands during the exposure to the emotional stimuli. The development of burnout is characterized by an increase in State Anxiety and fatigue, the desensitization to the emotionally accented information, an augmentation in social alienation and, eventually, manifests in changes in the brain response to emotional stimuli, which consist in the inhibition of high-frequency EEG components.